THE SEMANTIC OF COLOURS IN THE SIKKA LANGUAGE: A STUDY OF CONNOTATION - Sareng, Carmelita Riayanti; Uran, Stefanus Igolois Grenga; Kartini, Maria (Journal of Language and Literature, 2025)
The study aims to identify the names of colours in the Sikka Language, analyze the connotations associated with these colours, and investigate their functions within the Sikka community. Using a descriptive qualitative method, data were collected through observation, interviews, and data elicitation with native speakers from Wolomotong Village. Data analysis employed the Natural Semantic Metalanguage (NSM) theory to uncover the semantic and cultural meanings of colour terms. The findings reveal that the Sikka Language categorizes colours into three groups: basic colours, such as red (merak), white (bura), and black (mitan); derived colours, such as yellow (heret), green (daan), blue (daan wair) and brown(meran); and modern or borrowed colours, such as purple (langor), orange (heret duan), and pink (meran nurak). Colours in the Sikka Language carry profound connotative meanings tied to cultural and social contexts, including symbolic associations with beauty, courage, purity, and prosperity. Additionally, colours serve vital functions as markers of social identity, integral components of traditional rituals, and mediums for conveying cultural values. This study contributes to the field of semantics by offering insights into the interplay between language, culture, and cognition. Furthermore, it supports the preservation and promotion of local languages and cultural heritage.